THEOREM OF CHANGE IN THE ANGULAR MOMENTUM OF A SYSTEM WITH RESPECT TO A MOVING CENTER - To, Nguyen Dang (Vietnam Journal of Mechanics, 1987)
The Literatures of theorical mechanics only present, the theorem of change in the angular momentum of a system with respect to a fixed center; with respect to the center of mass ... In this paper we developed that theorem With respect to any moving center in relative and absolute motion of system. Having applied this theorem in many special cases of plane motion of a rigid body; we can write directly the differential equation without reactions that describes the rotation of that body so as its integration will be more convenient.